HAMILTONICITY OF CERTAIN CARTESIAN PRODUCTS OF GRAPHS - Tjaša Paj Erker (Journal of Energy Technology, 2023)
A graph is Hamiltonian if it contains a spanning cycle. In this paper, we examine the hamiltonicity of the Cartesian product of a tree with a path. We offer sufficient conditions for the Cartesian product of a tree with a path to be Hamiltonian.